Blowfish Advanced CS Untuk Solusi Keamanan Sistem Komputer Sekolah - Faisal Syafar; Halimah Husain; Sutarsih Suhaeb; Putri Ida; Supriadi (Sakura Digital Nusantara, 2023)
Data security and privacy are very important issues for businesses, colleges, the government, and even individuals. The TKJ Laboratory is where PKM events take place. Students are free to use the computers there as they please, as long as they don't break the security system on each one. The types of files that can be protected in this case are text-based document files, picture files, audio and video files that are stored digitally, and question files. In the Community Partnership Program, which had 15 participants, there were outcomes and goals. The program produced a guidebook on how to use Blowfish Advanced CS for computer system security cryptography and instructions on how to use Blowfish Advanced CS for computer system security cryptography. This study is a type of research called qualitative research. With a case study that aims to learn how to use the Blowfish Advanced CS tool to secure text messages, files, and documents with cryptographic data. The predicted outcomes of this PKM are 1) This key is combined to make the Blowfish algorithm stronger during the key setup process. 2) The Blowfish algorithm tool needs a key with at least 4 characters to encrypt the data file during the file/folder simulation. 3) The Blowfish method uses symmetric keys, which means that the simulation process always uses the same key to encrypt and decrypt data files and folders. The same key is also used to split and join files.